2008
DOI: 10.1002/ffj.1862
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil variability in Baccharis uncinella DC and Baccharis dracunculifolia DC growing wild in southern Brazil, Bolivia and Uruguay

Abstract: Essential oils of Baccharis uncinella DC and B. dracunculifolia DC collected from different wild populations growing in Bolivia, southern Brazil and Uruguay were analysed using gas chromatography and gas chromatographymass spectrometry techniques, to check for chemical variability. Cluster analysis led to the identi¼cation of two chemotypes for B. dracunculifolia, related to aromadendrane-or cadinane-derived components. As the timing of sampling of the plant material may have an in½uence on the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
(23 reference statements)
2
25
1
1
Order By: Relevance
“…It has been documented that EOs from aerial parts of B. uncinella obtained from Santa Catarina highlands (Ascari et al, 2009) and the state of Rio Grande do Sul, Brazil (Agostini et al, 2005;Frizzo et al, 2001Frizzo et al, , 2008 contain 3-60% of monoterpenes. The volatile metabolites in Baccharis are likely to be influenced by ecological and geographical factors as luminosity (Silva et al, 2006), rainfall regime (Ferracini et al, 1995), ground mineral content (Silva et al, 2007) and/or interaction with insects and predators (Damasceno et al, 2010), and the occurrence of chemotypes based on sesquiterpenes has been also reported (Frizzo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that EOs from aerial parts of B. uncinella obtained from Santa Catarina highlands (Ascari et al, 2009) and the state of Rio Grande do Sul, Brazil (Agostini et al, 2005;Frizzo et al, 2001Frizzo et al, , 2008 contain 3-60% of monoterpenes. The volatile metabolites in Baccharis are likely to be influenced by ecological and geographical factors as luminosity (Silva et al, 2006), rainfall regime (Ferracini et al, 1995), ground mineral content (Silva et al, 2007) and/or interaction with insects and predators (Damasceno et al, 2010), and the occurrence of chemotypes based on sesquiterpenes has been also reported (Frizzo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The volatile metabolites in Baccharis are likely to be influenced by ecological and geographical factors as luminosity (Silva et al, 2006), rainfall regime (Ferracini et al, 1995), ground mineral content (Silva et al, 2007) and/or interaction with insects and predators (Damasceno et al, 2010), and the occurrence of chemotypes based on sesquiterpenes has been also reported (Frizzo et al, 2008). It is therefore arguable that the distinct composition of BU-SC and BU-PR are related to ecological or genetics factors; it is to be expected that the differences observed in these samples CNS activities are consequent to these differences in composition.…”
Section: Discussionmentioning
confidence: 99%
“…Exception must be made to trans-b-guaiene, that was found here for the first time as a main component (7.9-6.1%) in essential oils from this species. 4,7,18,19,31,32,41,42 Baccharis dracunculifolia blossoms between January and April, a period of intense rainfall in the region where the plant material has been collected. However, the year of 2006 was one of the driest years in that region, with rainfall precipitations below the monthly average of six years before, and the plant material was collected on a sunny afternoon, after several days without rain, at the end of the drought period.…”
Section: J Braz Chem Soc 1044 Chemical Composition Similarity Betmentioning
confidence: 99%
“…1,2 On the other hand, the available data show that about 52 species from the Baccharis genus have been characterized on the basis of the chemical composition of their essential oils. The seasonal variability of the chemical composition of essential oils from some Baccharis species cultivated or growing in natura has already been reported, and it is widely accepted that ecological and geographical factors, such as luminosity, 3 rainfall regimes, 4 mineral content in the soil, 5 interaction with insects and predators, 6 and location and altitude, 7 exert influence on the content of volatile metabolites in plants of this genus. In addition, the extraction method used to obtain the essential oil may affect its chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…(Simões-Pires et al, 2005), B. dracunculifolia DC. (Frizzo et al, 2008;Fabiane, Ferronatto, dos Santos, & Onofre, 2008), B. erioclada DC. (Ferracini et al, 1995), B. platipoda DC.…”
Section: Discussionunclassified